2021
DOI: 10.1038/s41396-021-00975-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of chemotaxis and efflux pumps on nitrate reduction in the toxic regions of a ciprofloxacin concentration gradient

Abstract: Spatial concentration gradients of antibiotics are prevalent in the natural environment. Yet, the microbial response in these heterogeneous systems remains poorly understood. We used a microfluidic reactor to create an artificial microscopic ecosystem that generates diffusive gradients of solutes across interconnected microenvironments. With this reactor, we showed that chemotaxis toward a soluble electron acceptor (nitrate) allowed Shewanella oneidensis MR-1 to inhabit and sustain metabolic activity in highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…These results suggest that we are observing a direct response to the antibiotics. There is a growing body of work showing that flagella-based swimming can transport bacteria into regions of high antibiotic concentration 37 40 . However, to the best of our knowledge, there is no evidence of chemotaxis in response to the antibiotic gradients themselves.…”
Section: Resultsmentioning
confidence: 99%
“…These results suggest that we are observing a direct response to the antibiotics. There is a growing body of work showing that flagella-based swimming can transport bacteria into regions of high antibiotic concentration 37 40 . However, to the best of our knowledge, there is no evidence of chemotaxis in response to the antibiotic gradients themselves.…”
Section: Resultsmentioning
confidence: 99%
“…Depletion of chemotaxis-related genes has been shown to affect the antimicrobial susceptibilities of Aeromonas hydrophila [ 84 ]. Chemotaxis not only facilitates the ability of Shewanella oneidensis MR-1 to colonize but also maintains metabolic activity in regions where the antibiotic ciprofloxacin exhibits high toxicity [ 85 ]. The chemotaxis histidine kinase CheA has the ability to phosphorylate not only its specific response regulator CheY2, but also one of the response regulators involved in the pathway that mediates biofilm formation, FlmD [ 86 ].…”
Section: Resultsmentioning
confidence: 99%
“…RND efflux pumps are bacterial drug-resistance mechanisms that efflux a variety of hazardous substances to the outside of the cell, and there are five types of efflux pumps in E. coli [ 33 , 34 , 35 , 36 , 37 ]. It has previously been reported in the literature that the RND exocytosis pump plays a key role in the organic solvent tolerance and multidrug resistance of bacteria [ 38 , 39 ]. A previous study on PAH stress in Pseudomonas aeruginosa has shown that bacterial efflux pumps and transport genes play a key role in bacterial resistance to organic solvent toxicity [ 40 ].…”
Section: Discussionmentioning
confidence: 99%